1994
DOI: 10.1007/978-3-642-78820-8
|View full text |Cite
|
Sign up to set email alerts
|

Atoms in Strong Magnetic Fields

Abstract: Library of Congress Cataloging•in•Publication Data. Atoms in strong magnetic fields: quantum mechanical treatment and applications in astrophysics and quantum chaos 1 H. Ruder ... [et al.]. p. cm. Includes bibliographical references and index. \. Atomic transition probabilities. 2. Stars-Magnetic fields. 3. White dwarfs. 4. Neutron stars. 5. Quantum chaos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
271
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(283 citation statements)
references
References 0 publications
12
271
0
Order By: Relevance
“…Because of the enormous NS gravity, the outer layers of the NS atmosphere should be comprised of the lightest element present. If, in the absence of H, the NS has an He atmosphere, we still expect spectral features in the observed range if the magnetic field is ∼ G. In such a field the He atmos-12 3 # 10 phere is not completely ionized even at MK because of T ∼ 1 the large increase of the ionization potentials (Ruder et al 1994):…”
Section: Discussionmentioning
confidence: 91%
“…Because of the enormous NS gravity, the outer layers of the NS atmosphere should be comprised of the lightest element present. If, in the absence of H, the NS has an He atmosphere, we still expect spectral features in the observed range if the magnetic field is ∼ G. In such a field the He atmos-12 3 # 10 phere is not completely ionized even at MK because of T ∼ 1 the large increase of the ionization potentials (Ruder et al 1994):…”
Section: Discussionmentioning
confidence: 91%
“…The available nonmagnetic NS atmosphere models do not fit the observed spectrum, which is not surprising because the observed pulsations require a strong magnetic field. In recent years, there has been significant work on the structure and spectra of atoms in strong magnetic fields, mostly in fields below 10 13 G (see, e.g., Ruder et al 1994, Mori & Hailey 2002, and references therein). Based on these works, we can exclude some possibilities.…”
Section: Atomic Linesmentioning
confidence: 99%
“…T he response of atoms to high magnetic fields has been of interest for many decades [1][2][3][4] . It has been suggested that magnetic flux densities up to 10 5 T (1 gigagauss) exist on the surface of white dwarf and cataclysmic variable stars [5][6][7] .…”
mentioning
confidence: 99%
“…It has been suggested that magnetic flux densities up to 10 5 T (1 gigagauss) exist on the surface of white dwarf and cataclysmic variable stars [5][6][7] . This inference is based on a complex process that involves a combination of modelling the pattern of flux around the surface and up through the atmosphere of the star, and a search for transitions that are stationary with magnetic field [2][3][4] . These models are then compared with astrophysical spectra.…”
mentioning
confidence: 99%